Lack of association of CD44-rs353630 and CHI3L2-rs684559 with pancreatic ductal adenocarcinoma survival - Manuel Gentiluomo (Nature Portfolio, 2021)
Abstract Although pancreatic ductal adenocarcinoma (PDAC) survival is poor, there are differences in patients’ response to the treatments. Detection of predictive biomarkers explaining these differences is of the utmost importance. In a recent study two genetic markers (CD44-rs353630 and CHI3L2-rs684559) were reported to be associated with survival after PDAC resection. We attempted to replicate the associations in 1856 PDAC patients (685 resected with stage I/II) from the PANcreatic Disease ReseArch (PANDoRA) consortium. We also analysed the combined effect of the two genotypes in order to compare our results with what was previously reported. Additional stratified analyses considering TNM stage of the disease and whether the patients received surgery were also performed. We observed no statistically significant associations, except for the heterozygous carriers of CD44-rs353630, who were associated with worse OS (HR = 5.01; 95% CI 1.58–15.88; p = 0.006) among patients with stage I disease. This association is in the opposite direction of those reported previously, suggesting that data obtained in such small subgroups are hardly replicable and should be considered cautiously. The two polymorphisms combined did not show any statistically significant association. Our results suggest that the effect of CD44-rs353630 and CHI3L2-rs684559 cannot be generalized to all PDAC patients.